التحيّز المعرفي في تفسير الفقر نقد لمنظور المدرسة السائدة في علم الاقتصاد (International Institute of Islamic Thought, 2017)
يرى أتباع المدرسة الاقتصادية السائدة أنَّ علم الاقتصاد يخضع لمنهج موضوعي عالمي ومحايد، وهم مطمئنُّون إلى خلوِّه من أيِّ تحيُّز أو تحكّم قيمي. غير أنَّ الـمُطَّلِع على فلسفة العلم المعاصرة يدرك أنَّ فكر المدرسة السائدة ما زال متخلِّفاً عن ركب فلسفة المعرفة؛ لتمسَّكِه بمناهج فلسفات الحداثة الوضعية الصُّلبة، التي تؤمن بإمكانية تحقيق الموضوعية في علم الاقتصاد بصورة تقارب تحقُّقها في علوم المادة وعلوم الأحياء، وحتى الرياضيات. وتهدف هذه الدراسة إلى الكشف عن مظاهر التحيُّز إلى هذا النموذج المعرفي لدى هذه المدرسة في تفسيرها لظاهرة الفقر، وتعتمد الدراسة أسلوب النقد لكشف الغطاء عن عدم علمية هذا النموذج، وإظهار الأيديولوجيا الكامنة خلف تلك التفسيرات التي حالت دون إحراز أيِّ تقدُّم لعلم الاقتصاد تجاه مسألة الفقر. The majority of economists believe that economics is subject to a universal objective and neutral methodology, reassured to be free from any bias or value judgment. The contemporary philosophy of science, however, is aware that this prevailing school ideology is still lagging behind the philosophy of knowledge; as it adheres to the rigid modes of positivistic modernity, which believes Economics might achieve objectivity of economics close to what has been achieved in sciences of matter, biology, and even mathematics. This study aims to reveal the manifestations of bias in this school of thought when it interprets the phenomenon of poverty. The study relies on the method of criticism to uncover this un-scientific model, and the ideology behind those explanations that prevented any progress of economics on the issue of poverty.